Loading web-font TeX/Main/Regular

4.5(x-4)+1.5x=2(4x-4)-1

Simple and best practice solution for 4.5(x-4)+1.5x=2(4x-4)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.5(x-4)+1.5x=2(4x-4)-1 equation:



4.5(x-4)+1.5x=2(4x-4)-1
We move all terms to the left:
4.5(x-4)+1.5x-(2(4x-4)-1)=0
We add all the numbers together, and all the variables
1.5x+4.5(x-4)-(2(4x-4)-1)=0
We multiply parentheses
1.5x+4.5x-(2(4x-4)-1)-18=0
We calculate terms in parentheses: -(2(4x-4)-1), so:
2(4x-4)-1
We multiply parentheses
8x-8-1
We add all the numbers together, and all the variables
8x-9
Back to the equation:
-(8x-9)
We add all the numbers together, and all the variables
6x-(8x-9)-18=0
We get rid of parentheses
6x-8x+9-18=0
We add all the numbers together, and all the variables
-2x-9=0
We move all terms containing x to the left, all other terms to the right
-2x=9
x=9/-2
x=-4+1/2

See similar equations:

| 10/16=15/6x | | -20=56n-12n^2 | | 2(x-3.50)=5.80 | | w^2-7w-35=0 | | 9m2+18m+-2=5 | | (2x+125)=(x+163) | | -7x-4=6x-108 | | 2(x-3.50)=5.80 | | 5x^2-3x;x=2 | | 3x-8=-7+2x | | 7r^2+63r=-56 | | 3w+4w-1=12+3/5(w+1) | | 9y-7y-13=10.17 | | (-2p-8)/4=6 | | 4x-16=12-5x | | |3x-4|=20 | | v/4+5=17 | | -11r+11(6r+4)=55+10r | | -6x-2x=40 | | 3(w+2)-7w=34 | | 4(x-5)-5=6x=33 | | n^2=14+5n | | 6(x+1)+5=13-2(1-3x) | | 2(2b-1)=15 | | C(x)=0.85x+8 | | w=3/8=1/4 | | 4t+2+5t-8t=3+6 | | 18x+25=24x+13 | | 60+132d-36=-d+7 | | X=525-(63-5x) | | 4t+2+5t-8t=0 | | (5x+9)=(3x+5) |

Equations solver categories